The quantity and amorphicity determination of oxidable coke on the zeolite-containing catalysts of cracking; Petroleum and Coal; Vol. 61, iss. 5 - Nazarova G. Yu. Galina Yurievna; Ivashkina E. N. Elena Nikolaevna; Oreshina A. A. Aleksandra Aleksandrovna; Burumbaeva G. R. Galiya Rashidovna; Vymyatnin E. K. Evgeny Konstantinovich; Seytenova G. Zh. Gayni Zhumagalievna; Artcer T. V. Tatiana Vladimirovna (2019, 2019)
Title screen